Technology entrepreneurship : creating, capturing, and protecting value - Duening, Thomas N. (Academic Press, 2010)
Recognizing the unique needs of the technology startup, Duening focuses on intellectual property development, funding, and marketing/selling more than other texts in this market. Extensive use of technology examples, case studies, and assignments keeps the book relevant and motivating for engineering students. A full supplements package, including instructor manual and lecture notes, makes it easy to get the course up and running. * rich in case studies, examples, and in-chapter elements that focus on the challenges of launching and operating a technolog.